Strategi Komunikasi Pembangunan Tim Promosi Kesehatan Puskesmas Polokarto Melalui Program Desa Siaga - Agus Triyono; Yanuar Adi Wibowo (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
The development program has three components namely development communications, development programs containing ideas about development programs, and the community. This research focused on community empowerment in the health area through Desa Siaga program. Desa Siaga is the state of a region that is ready to implement health empowerment independently. The purpose of this research was to find out the development communication strategy of the Health Promotion Team, the Community Health Care of Polokarto, through Desa Siaga program in Bulu Village, Polokarto, Sukoharjo. It used a descriptive qualitative method. This study used in-depth interviews with three informants and observation. Informants were selected using snowball sampling technique. The findings demonstrated that the team successfully implemented Desa Siaga program using the 5P technique (Possibility, Reinforcement, Protection, Support, and Maintenance). The findings also indicated that Desa Siaga program as a program introduced by Puskesmas Promotion team Polokarto received a positive response from the community by forming an organization to launch the program that is Village Health Forum.